SIX SIGMA AS A TOTAL QUALITY MANAGEMENT TOOL - C.E. Odendaal; S.J. Claasen (South African Journal of Industrial Engineering, 2012)
The ultimate goal of most companies is to make money and even more money in the future. Part of increasing profits means reducing costs, improving quality and increasing throughput. This paper describes the use of Six Sigma methodologies as a tool in achieving Total Quality Management in the manufacturing environment, with specific emphasis on power transformer manufacturing. The concepts encompassed by Six Sigma are included, their relevance explained and some early results are shared. The measure, analyse, improve and control cycle is the main emphasis of this paper. It is concluded that by adopting Six Sigma as a Total Quality Management tool, company bottom lines are improved.